2018
DOI: 10.1071/sh17217
|View full text |Cite
|
Sign up to set email alerts
|

Use of poppers and HIV risk behaviours among men who have sex with men in Paris, France: an observational study

Abstract: The use of inhaled nitrites, or poppers, among men who have sex with men (MSM) is prevalent, yet has been associated with HIV seroconversion. We surveyed 580 MSM from a geosocial networking smartphone application in Paris, France, in 2016. Of the respondents, 46.7% reported popper use within the previous 3 months. Regression models adjusted for sociodemographic characteristics found that the use of poppers was significantly (P<0.05) associated with the following during the prior 3 months: condomless anal inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
1
5
1
Order By: Relevance
“…Consistent with these data, in a prior analysis of survey data from 580 geosocial network app-using MSM in Paris, France (33), we found that poppers use was quite prevalent, with nearly half of survey respondents reporting poppers use within the prior three months. In addition, we found that popper users were more likely than non-users to practice CAI, engage in group sex, and report a diagnosis of an STI within the past three months, reaffirming the argument that MSM who use poppers represent a subgroup at higher than average risk for HIV seroconversion, and therefore would be appropriate candidates for PrEP.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with these data, in a prior analysis of survey data from 580 geosocial network app-using MSM in Paris, France (33), we found that poppers use was quite prevalent, with nearly half of survey respondents reporting poppers use within the prior three months. In addition, we found that popper users were more likely than non-users to practice CAI, engage in group sex, and report a diagnosis of an STI within the past three months, reaffirming the argument that MSM who use poppers represent a subgroup at higher than average risk for HIV seroconversion, and therefore would be appropriate candidates for PrEP.…”
Section: Introductionsupporting
confidence: 86%
“…Although popper use has been shown to be highly correlated with HIV seropositivity, due to both high rates of sexual risk behavior (2426, 33) and direct vasodilatory effects of inhaled nitrites (32), we found that popper users were not more likely to be using PrEP than non-popper users. Indeed, while 26.4% of popper users reported themselves as “definitely” an appropriate candidate for PrEP, only 7.2% reported current PrEP use.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Use of intoxicants during sex was selected by respondents from a pre-defined list consisting of alcohol, amphetamine, cannabis, gamma-hydroxybutyrate (GHB) or gamma-butyrolactone (GBL), heroin, ketamine, cocaine, mephedrone, methylenedioxy-methamphetamine (MDMA) or ecstasy, methamphetamine/ice, poppers (alkyl nitrate inhalants), or other substance. Two variables regarding intoxicants were recoded for analysis; Hard drug use during sex , where alcohol, poppers, cannabis, and ‘other’ were excluded, and Poppers use during sex , motivated by the debated association between poppers use and behaviors associated with HIV and STI [ 34 ]. Sex abroad was assessed by asking the respondents if they had had sex outside Sweden during the previous 12 months, motivated by the high proportion of new HIV diagnoses in Sweden being contracted abroad [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from specific countries revealed nitrite inhalants use was significantly associated with risky sexual behaviors [ 13 , 24 , 25 ]. However, only a small number of studies in China reported the association between nitrite inhalants use and sexual behaviors, like seeking male sexual partners via the internet, having multiple sex partners and practicing UAI [ 16 , 17 , 26 ].…”
Section: Discussionmentioning
confidence: 99%